El costumbrismo feminista de Gertrudis Gómez de Avellaneda - Albin, María C. (Anales de Literatura Hispanoamericana, 2008)
The essay “The lady of good taste”, written by Gertrudis Gómez de Avellaneda and published in 1843 in the magazine Album del Bello Secso, confirms the dialectical struggle which the author maintains with the society of her epoch in defence of women’s equality. Throughout the text, which follows the local colour model of Mesonero Romanos, the Cuban fights for women’s right to equality and undermines Rousseau’s gender discourse.